John the Baptist and Jesus the Baptist: A Narrative Critical Approach - Taylor, Joan E. 1958-; Adinolfi, Federico (2012)
Narrative criticism is not usually employed as a means of exploring historical knowledge. However, in this article it is argued that narrative patterns can be indicative of history masked by overt rhetoric. In the narrative of Jesus’ ministry in Galilee the Gospel of Mark includes the persistent presence of water, often in combination with wilderness places and crowds. This pattern replicates the same features associated with John the Baptist, creating a narrative template for Jesus continuing John’s baptism, which Mark knew to be concerned with ritual purity, and yet explicit mention of Jesus’ baptizing is avoided. Mark focuses instead on Jesus as the promised immerser in Holy Spirit, proven by his healings and exorcisms, in which purification flows outwards from him. Mark points to a historical scenario in which Jesus’ healings and exorcisms are understandable within the same purity framework that governed water immersions: they were remedies for the most stubborn cases of people who, because of their chronic ailments and disabilities, were unable to obtain the inner purity that was normally established by repentance and forgiveness of sins. Jesus then fulfils John’s prediction and continues John’s work.
Keywords: Baptism -- healing -- Holy Spirit -- immersion -- John the Baptist -- narrative criticism -- ritual purity